Impact of Covid-19 pandemic on Ophthalmic Emergency Department in an Italian tertiary eye centre. Issue 1 (January 2022) - Franzolin, Elia; Casati, Stefano; Albertini, Ottavia; Antonelli, Giulio; Marchetti, Pierpaolo; Bonora, Antonio; Marchini, Giorgio
Purpose: To evaluate the effects of the COVID-19 pandemic on the Ophthalmic Emergency Department (OED) activity of the tertiary eye centre of Verona. Methods: OED reports of patients visited during lockdown (COVID-period) and in the corresponding period of 2017, 2018 and 2019 (COVID-free period) have been retrieved to draw a comparison. Patients' demographic and clinical data recorded and analysed are the following: age, gender, previous ocular history, aetiology, symptoms onset, type of symptoms, discharge diagnosis, urgency and severity of diagnosis. Results: OED consultations dropped from 20.6 ± 7.3 visits/day of the COVID-free period to 8.6 ± 4.6 visits/day of the COVID-period. In the COVID-period patients waited longer before physically going to the OED, lamented more vision loss and less redness and reported a higher percentage of traumatic events when compared to the COVID-free period. A significant reduction of ocular surface conditions occurred, while vitreo-retinal disorders increased. Overall, both urgency and severity of diagnosed diseases raised significantly in the COVID-period. Conclusion: The COVID-19 pandemic drove a significant reduction of the overall OED activity. People with less urgent and milder conditions preferred to wait and endure their ocular discomfort for a few days rather than leaving home and risking to contract the infection. Our analysis highlights how several times the OED is used improperly by patients diagnosed with non-urgent disorders. A more accurate use of the OED would allow a reduction of management costs and the avoidance of overcrowding, which can lead to delays in the care of patients that really need assistance.